Influence of culture vessel volume and ventilation on in vitro culture and adenosine accumulation of Anoectochilus setaceus Blume - Luận, Vũ Quốc; Nam, Nguyễn Bá; Hiền, Vũ Thị; Huy, Nguyễn Phúc; Tùng, Hoàng Thanh; Luận, Trần Công; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2018)
Anoectochilus setaceus is a medicinal plant used as a traditional medicine as well as nutritious products for health care in China and many Asian countries. In conventional propagation, the the vessel type, material and volume lead to differences in the moisture content between the internal and external conditions which result in great impact on the quality of in vitro plantlets as well as subsequent growth at nursery. In this study, several factors affecting the multiplication and regeneration of A. setaceus cultured in vitro were investigated. The highest percentage of shoot regeneration (52.88%) from ex vitro stem nodes was obtained when explants were cultured on SH medium supplemented with 1 mg/l BA, 30 g/l sucrose with cotton wool plug as the substrate and pH of the medium was adjusted to 5.8 prior to autoclaving. In the present study, culture vessel volume and ventilation culture conditions indicated to have effect on shoot quality. Results showed that 3-liter Erlenmeyer flasks in combination with ventilation caps resulted in better shoot growth and development (shoot height: 10.75 cm; 9.45 leaves per shoot; fresh- and dry- weight of 2.45 and 0.219 g per shoot, respectively; leaf diameter: 2.85 cm and SPAD: 39.99). Results of chromatography (TLC) analysis indicated that explants gave the same Rf value as that of authentic Adenosine. Qualifying Adenosine using TLC showed that extracts of shoots cultured on solid and liquid medium (ventilation plastic bag), and that of shoots cultured in 3-liter vessel with liquid medium (with and without ventilation) gave the same pattern in the respects of color and Rf value